2023
DOI: 10.31849/utamax.v4i3.9570
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Perceptions of Extensive Reading Intervention: Evidence from Universitas Hasanuddin Non-English Freshmen

Abstract: This paper reports the findings drawn from a six-month survey on first-year students’ perception of Extensive Reading intervention in a basic general English course program at Hasanuddin University. This survey study aimed to reveal the extent to which the samples agreed on some aspects of language learning’s positive impacts from attending a reading intervention semester. Other aspects were also examined to the degree of improvement, such as students’ beliefs about eclecticism, self-confidence, and social ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although some studies have explored the perceptions of EFL learners, they have studied perceptions about the ER approach alone (Al Aghar et al, 2023;Pammu et al, 2022;Ateek, 2021;etc.). These studies have shown that learners believed the use of ER was of great benefit to them and they always preferred to be engaged in abundant free reading both inside and outside the classrooms.…”
Section: Perceptions Of Efl Learners About the Integrated Use Of Inte...mentioning
confidence: 99%
“…Although some studies have explored the perceptions of EFL learners, they have studied perceptions about the ER approach alone (Al Aghar et al, 2023;Pammu et al, 2022;Ateek, 2021;etc.). These studies have shown that learners believed the use of ER was of great benefit to them and they always preferred to be engaged in abundant free reading both inside and outside the classrooms.…”
Section: Perceptions Of Efl Learners About the Integrated Use Of Inte...mentioning
confidence: 99%